Identifying targets for interventions to improve communication between primary and secondary care: a qualitative study of referrals to adult NHS hearing aid services - Khan, Sobia; Loughran, Michael T.; Armitage, Christopher J.; Leverton, Ted; Mehta, Nishchay; Oliver, Francesca; O’Driscoll, Martin; Nassar, Greg; Sutton, Chris J.; Lewis, Kathryn; Dawes, Piers; Bower, Peter; et al. (Archives of public health = Archives belges de santé publique, 2025)
Background Improving communication between NHS primary and secondary care services should reduce inefficiencies, improve patient care, and provide a source of accurate data for audit and research. Using general practice (primary care) and adult hearing aid services (secondary care) as examples, this study aimed to investigate the: (i) information primary care want from secondary care services during referral processes and what information secondary care can provide, (ii) barriers and facilitators for coding and providing this information, and (iii) targets for interventions to improve communication. Methods Qualitative interview study. Twenty-nine semi-structured interviews were conducted with primary and secondary care staff in North West England, informed by the capabilities, opportunities, and motivations model of behaviour change (COM-B). A thematic analysis with findings mapped to the Theoretical Domains Framework (TDF) was used to identify barriers and facilitators to the recording and communication of hearing health information, as well as behavioural determinants to target in future interventions. Results Four key TDF domains were identified as potential determinants to target for future interventions: (1) time and resources (e.g., environmental context and resources) are stretched across the two sectors; (2) fatigue, tiredness, and cognitive overload affecting workflow (e.g., memory, attention, and decision processes), particularly adult hearing aid service administration; (3) adult hearing aid services are unaware if their letters are read by general practice, or if the level of information they send is appropriate (e.g., knowledge); and (4) difficulties communicating with general practice and a lack of feedback is causing reduced motivation from adult hearing aid services to make direct contact (e.g., beliefs about consequences). Conclusions This study identified four theoretically-derived variables that are barriers to communication and record sharing, and highlights how these can be translated into potential interventions (e.g., simplified coding). Further work is required to test interventions developed using behaviour change theory.